Protein food consumption among students in a Nigerian university: a demand modelling (2022)
Adequate consumption of protein is indispensable for human growth and health. Nigeria has a high burden of protein deficiency with attendant loss of economic productivity and high health bills due to ill-health. Owing to paucity of information on demand for protein foods among Nigerian youths, the study assessed the demand for protein foods among students of the University of Ibadan, Ibadan, Nigeria. The data collected from 300 students through a multi-stage sampling procedure were analysed using descriptive statistics and Quadratic Almost Ideal System model (QUAIDS). The results have shown that some of the price coefficients expectedly had a negative relationship with the expenditures. The youths also spent more on beans and chicken but spent less on groundnut. Furthermore, expenditure elasticities of all protein foods were positive. Moreover, expenditure elasticities for beans, eggs, beef and goat meat showed that they were necessities goods, whereas chicken, turkey, soy milk, pork, groundnut and milk were luxury goods. Both compensated and uncompensated elasticity showed that own-price elasticities for the selected protein food items were inelastic, with the exception of goat meat. Demand for protein foods was influenced by own-prices of the protein foods, prices of other protein foods and being a male student. In order to meet their daily dietary needs within a limited budget, students should substitute expensive protein sources like chicken, goat meat, beef and turkey with cheaper ones like groundnut, soymilk, beans and eggs in their diets.